Measuring repetitive thinking in Iran: Psychometric properties of Persian version of Perseverative Thinking Questionnaire. (1st October 2019) - Kami, Maryam; Moloodi, Reza; Mazidi, Mahdi; Ehring, Thomas; Mansoori, Amin Khaje; Nodooshan, Mojgan Bakhshi; Mazinani, Zahra; Molavi, Mohammad-Reza; Momeni, Fereshte
Abstract: Objective: The aim of the present study was to evaluate the factor structure as well as the validity and reliability of the Persian version of Perseverative Thinking Questionnaire (PTQ). Method: Data were collected in three samples. A student sample ( N  = 894) completed the Generalized Anxiety Disorder Scale (GAD-7), the Difficulties in Emotion Regulation Scale (DERS) and the PTQ. Participants from the general population ( N  = 252) filled out a battery of questionnaires including the Penn State Worry questionnaire (PSWQ), the Ruminative response scale (RRS), the Depression, Anxiety, Stress Scale-21 (DASS-21) and the PTQ. Finally, psychotic inpatients ( N  = 193) filled in the PTQ, only. Results: Confirmatory factor analysis indicated that the second-order model with three lower-order factors model showed adequate fit with the data in all three samples. In addition, the PTQ had good internal consistency and test-retest reliability. As to validity, the PTQ scores showed positive correlation with the PSWQ, RRS, DERS, GAD-7 and DASS-21. In addition, the PTQ was found to discriminate the clinical sample from student and general population samples. Conclusions: The findings provided preliminary support for validity and reliability of the scores derived from Persian version of the PTQ. Highlights: The original model of PTQ showed adequate fit with the data of Iranian samples. The PTQ showed adequate to good reliability and satisfactory convergent validity. The PTQ can distinguish between clinical, student, and general population samples.